FAKTOR–FAKTOR YANG MEMPENGARUHI PEMBIAYAAN MUDHARABAH DI BANK MUAMALAT INDONESIA: Bahasa Indonesia - Bella Adni; Rafidah Rafidah; Novi Mubyarto (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2022)
Raising funds from third parties of Islamic banks is an indicator of the number of Islamic banks disbursing financing, if more Islamic banks channel financing, the more profit margin returns. This study aims to analyze the factors that influence mudharabah financing at Bank Muamalat Indonesia in 2015-2020. Mudharabah financing will be viewed from Third Party Funds, Return on Assets, Capital Adequacy Ratio, Non Performing Financing and Total Assets. Bank Muamalat Indonesia financial report data for 6 years from 2015-2020 on a quarterly basis so that there are 24 samples. The data were analyzed using multiple linear regression. Partially, the Third Party Fund variable has a negative and significant influence on mudharabah financing. The ROA, NPF and Total Assets variables have a positive influence in distributing mudharabah financing, while the CAR variable has no effect on the distribution of mudharabah financing. However, simultaneously the variables of TPF, ROA, CAR, NPF, and Total Assets affect the distribution of mudhaarabah financing.